Investigation of Affordable Electrode Material Combinations in Electrochemical Biosensors - Toru Nohgi; Siyu Jia; Kenji Ueda; Jun Kameoka (Proceedings)
This study investigated carbon-based electrode materials for the application of wearable biosensors measuring uric acid concentration [...]